Statistical optimization of stress relieving parameters on closed cell aluminium foam using central composite design - Puspitasari, D. (International OCSCO World Press, 2018)
Purpose: This study concerns about the influence of stress relieving parameters on the hardness of closed cell aluminium foam using central composite design. Design/methodology/approach: The responses of three stress relieving parameters: heating temperature, holding time and stabilization temperature are studied and analysed through 20 experimental runs designed according to central composite design. The results of microhardness test corresponded to the microstructural evaluation of closed-cell aluminium foam using optical microscope. Analysis of Variance (ANOVA) technique is employed to study the significance of each parameter on the microhardness property. In this process the design has five levels for each parameter. The stress relieving process of the samples were performed using a vacuum furnace. The hardness test was conducted using a micro hardness tester LM247AT and the microstructure of the samples were obtained using optical microscopy technique. Findings: It was found that the highest value of hardness of 192.78 HV was obtained when the stress relieving process is set with the following parameters: heating (500°C); holding time (120 min) and stabilization temperature (450°C). Since higher heating temperature and longer holding time produce sample with larger grain size and has an adverse effect on the hardness value. Research limitations/implications: Liquid metal and powder metallurgical processing still produces a non-uniform and poorly reproducible cellular structure. This cellular structure demonstrates poor quality difference on decomposition and melting temperature, called anisotropic early expansion. Originality/value: To improve the poor cellular structure quality, stress relieving method is proposed in this study. Stress relieving method can improve the microstructure of the material. © International OCSCO World Press. All rights reserved. 2018.